Implementasi Metode Bernyanyi untuk Meningkatkan Hasil Belajar Siswa di SD/MI - Suparlan, Suparlan (rogram Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2023)
Effective learning methods are those that efficiently achieve educational goals while considering learners’ characteristics. Singing emerges as a highly favored approach among children due to its lively and joyful nature, fostering active participation. Learning outcomes, a result of the interplay between teaching and learning activities, are elucidated through the understanding of “results” and “learning.” “Results” signify the functional changes resulting from an activity, while “learning” represents an individual’s efforts to undergo behavioral change. Learning is a directed process aimed at achieving predetermined competencies, involving activities such as observing, creating, problem-solving, listening, and practicing. The culmination of these activities defines the acquired abilities of students after the learning process. Singing, as a method, exemplifies its effectiveness through its ability to create a positive and dynamic learning environment, engaging children in a participatory and enjoyable manner.